Role of inflammation in environmental neurotoxicity - Aschner, Michael, 1955-; Costa, Lucio G., 1954- (Advances in neurotoxicology, 2019)
Role of Inflammation in Environmental Neurotoxicity, Volume Three, in this comprehensive serial, addresses contemporary advances in neurotoxicology by providing authoritative review articles on key issues in the field. Edited by leading subject experts, topics of note in this new release include Neuroinflammation (Introduction), Organophosphates, Lead, Manganese, Drugs of abuse, Peripheral vs central inflammation, Air pollution, Developmental neurotoxicity, Ethanol, and the Blood brain barrier, amongst other topics.